2019
DOI: 10.1029/2019sw002296
|View full text |Cite
|
Sign up to set email alerts
|

Superposed Epoch Analysis of the Energetic Electron Flux Variations During CIRs Measured by BD‐IES

Abstract: The flux variations of energetic electrons is one of the most important topics to understand dynamic processes in the space environment and the forecast for high-energy electron burst. BeiDa Image Electron Spectrometer (BD-IES), an imaging energetic elecstron spectrometer onboard a Chinese navigation satellite at an inclined geosynchronous orbit, can provide 50-600 keV electron flux data, which is used to investigate electron flux variations at GEO orbit during Co-rotating Interaction Region events (CIRs). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…One example of this approach is the use of superposed epoch analysis to focus electron flux decreases termed “dropouts,” seen in GPS data, following high speed streams (Morley et al., 2010), and subsequently examined using low‐Earth POES observations (Meredith et al., 2011, Hendry et al., 2012). The value of similar approaches has been demonstrated more recently in multiple studies, examples being: using Van Allen Probes to investigate the impact of differing drivers (Katsavrias, Daglis, & Li, 2019) and separating adiabatic and nonadiabatic effects (Murphy et al., 2018), MLT‐resolved dynamics using POES measurements around substorm cluster events (Rodger et al., 2019), GPS‐measured changes in electron fluxes during EMIC scattering events (Hendry et al., 2021), and BD‐IES observed electron flux variations during high speed streams (Yin et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of this approach is the use of superposed epoch analysis to focus electron flux decreases termed “dropouts,” seen in GPS data, following high speed streams (Morley et al., 2010), and subsequently examined using low‐Earth POES observations (Meredith et al., 2011, Hendry et al., 2012). The value of similar approaches has been demonstrated more recently in multiple studies, examples being: using Van Allen Probes to investigate the impact of differing drivers (Katsavrias, Daglis, & Li, 2019) and separating adiabatic and nonadiabatic effects (Murphy et al., 2018), MLT‐resolved dynamics using POES measurements around substorm cluster events (Rodger et al., 2019), GPS‐measured changes in electron fluxes during EMIC scattering events (Hendry et al., 2021), and BD‐IES observed electron flux variations during high speed streams (Yin et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated more recently in multiple studies, examples being: using Van Allen Probes to investigate the impact of differing drivers (Katsavrias, Daglis, & Li, 2019) and separating adiabatic and nonadiabatic effects (Murphy et al, 2018), MLT-resolved dynamics using POES measurements around substorm cluster events (Rodger et al, 2019), GPS-measured changes in electron fluxes during EMIC scattering events (Hendry et al, 2021), and BD-IES observed electron flux variations during high speed streams (Yin et al, 2019).…”
mentioning
confidence: 99%
“…These precipitating energy fluxes are also comparable to those induced by hiss waves during disturbed conditions (∼0.3–1 normalenormalrnormalg·normalcm2·s1 $\mathrm{e}\mathrm{r}\mathrm{g}\cdot \mathrm{c}{\mathrm{m}}^{-2}\cdot {\mathrm{s}}^{-1}$, Ma et al., 2021). Note that this comparison is rather inaccurate, since the simulation results largely depend on the electron distribution before the ULF wave occurrence, which could be enhanced significantly during geomagnetic storms and/or substorms (Kataoka & Miyoshi, 2006; McPherron, 1979; Yin et al., 2019). The enhanced source population could in turn lead to enlarged precipitation and therefore an enhanced ground‐based response.…”
Section: Discussionmentioning
confidence: 99%
“…The pin‐hole imaging sensor head with a spin‐stabilized satellite platform can provide three‐dimensional measurements of medium‐energy electrons. A similar pin‐hole imaging sensor head design has been successfully used in the BeiDa imaging electron spectrometer (BD‐IES) and energetic electron detection package (EEDP) deployed on Chinese navigation satellites to achieve multi‐directional measurements of medium‐energy electrons in medium Earth orbit (MEO) and geosynchronous equatorial orbit (GEO) (Chen, Zong, Zou, Wang, et al., 2020; Chen, Zong, Zou, Zhou, et al., 2020; Hao et al., 2020; Li, Zhou, Zong, Chen, et al., 2017; Li, Zhou, Zong, Rankin, et al., 2017; Liu et al., 2018; Wang et al., 2017; Ye et al., 2021; Yin et al., 2019; Zong et al., 2016, 2018; Zou et al., 2018, 2019). All of these satellites are three‐axis‐stabilized platforms.…”
Section: Instrument Overviewmentioning
confidence: 99%